Common Fixed Points of Two Pairs of Selfmaps Satisfying $(E.A)$-property in $b$-metric Spaces Using a New Control Function - Venkata Ravindranadh Babu Gutti; Dula Tolera Mosissa (International Journal of Mathematics And its Applications, 2017)
In this paper, we apply the $(E. A)$-property to prove the existence and uniqueness of common fixed points of four selfmaps in the setting $b$-metric spaces using a new control function. We provide an example in support of our results. Our results generalize the fixed point results of Ozturk and Radenovic [11].